Effects of corm size and benzylaminopurine on plantain proliferation in two propagation environments (2022)
Macropropagation of plantain in a thermal chamber is an economic technology, effective as a method of phytosanitary cleaning, and efficient to enhance the production of seedlings. The aim of the research was to evaluate the effects of corm size (CZ) and benzylaminopurine (BAP) on the proliferation of plantain seedlings cv. Barraganete in two propagation environments (PE). The treatments consisted of two levels of BAP (with and without BAP), three CZ (2±0.5, 4±0.5 and 6±0.5 kg) and two PE (thermal chamber and raised bed). The variables evaluated were budding time (days), multiplication rate (MR) per unit (seedlings per corm) and per area (seedlings per m2). The budding time was significantly influenced (p < 0.05) by the PE, where the thermal chamber advanced the emergence of shoots by 12 days, with respect to the raised bed. The MR of seedlings per corm and m2 were significantly influenced (p < 0.05) by BAP x PE and CZ x PE interactions, where the highest production of seedlings per corm occurred within the thermal chamber with BAP and corms of 6±0.5 kg, while the production of seedlings per m2 was higher with 2±0.5 kg corms under the same thermal chamber conditions and with BAP. The main effects results reported that with BAP there was a 30 and 31% increase in MR per corm and per m2, respectively, in relation to the treatment without BAP. Within the thermal chamber, the MR per corm and per m2 increased by 44% with respect to the raised bed. Regarding the effect of CZ, larger corms reached a higher individual MR, while those of smaller size reached a higher MR per area. It is recommended to use a thermal chamber and BAP to massify the production of plantain seedlings via macropropagation.